2018
DOI: 10.17159/sajs.2018/a0285
|View full text |Cite
|
Sign up to set email alerts
|

Searching for David within the Goliath of alien woody plant invasions in the Western Cape Province

Abstract: Despite a few victories in which biocontrol has contained some species of invasive alien woody plants, the war to contain alien invasions and to prevent them from threatening the exceptional plant diversity of the Cape Floristic Region is largely being lost. 1-8 Indeed, these invading plants are estimated to be expanding their range at an average rate of 7% per year. 9 http://www.sajs.co.za

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The presence or absence of alien trees in fynbos and encroaching native trees in grassland environments of South Africa have been linked to a wide range of nutrients, soil properties, and soil treatments, including pH, acid saturation, Mg, Ca, Mn, Cu, Zn, B, P, and N-fertilisation (Mills and Allen 2018;Mills et al 2017). Unpublished data collected from 25 diverse sites across South African Fynbos, Grassland and Savanna sites have shown that soils in sub-sites relatively poor in boron or relatively rich in phosphorus tend to be less wooded than adjacent sub-sites.…”
Section: Soilsmentioning
confidence: 99%
“…The presence or absence of alien trees in fynbos and encroaching native trees in grassland environments of South Africa have been linked to a wide range of nutrients, soil properties, and soil treatments, including pH, acid saturation, Mg, Ca, Mn, Cu, Zn, B, P, and N-fertilisation (Mills and Allen 2018;Mills et al 2017). Unpublished data collected from 25 diverse sites across South African Fynbos, Grassland and Savanna sites have shown that soils in sub-sites relatively poor in boron or relatively rich in phosphorus tend to be less wooded than adjacent sub-sites.…”
Section: Soilsmentioning
confidence: 99%